Approximation of Functions in Lp, Î± (I) (0 < p < 1) - Jassim, Saheb K.; Shamkhi, Israa Z. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper we show that the function , () p fLI Î± âˆˆ ,0<p<1 where I=[-1,1] can be approximated by an algebraic polynomial with an error not exceeding , 1 ( , , ) kp ft n Ï• Î±Ï‰ where , 1 ( , , ) kp ft n Ï• Î±Ï‰ is the Ditizianâ€“Totik modules of smoothness of unbounded function in , () p LI